Persepsi Guru Tentang Pola Manajerial Kepala Sekolah DanMotivasi Guru Terhadap Kinerja Guru Sekolah MenengahPertama Negeri Se Kecamatan Banjarejo Kabupaten BloraTahun Ajaran 2016/2017 - Retyasari, Rosa atka; , Drs.Samian,M.M (2017)
This study aims to determine 1) the influence of teachers 'perceptions about the managerial patterns principals on teacher performance, 2) the influence ofmotivation of teachers on teacher performance, 3) influence teachers' perceptionsabout the principal managerial patterns and motivation of teachers on teacherperformanceThe method used in this research use descriptive research with quantitative approach.The research was conducted at SMP N 1 Banjarejo and SMP N 2 BanjarejoBlora.Technique of district data collection using questionnaires and documentation.Data analysis techniques used to test hypotheses using multiple linear regressionanalysis, partial test, test simultaneous and effective contribution, donation relatif.The conclusion of this research is 1). teachers' perceptions of managerial patternpositive influence on teacher performance obtained > , which is 2,171 >2,004 with significant value <0.05 is 0.036 with a magnitude of 29% and 9.6%effective donation . 2) motivation of teachers has a positive effect on the 2performance of teachers. Obtained > ,, which is 2,249 > 2,004 with significant value 0.029 <0.05. As for the effective donation at 23% relative donation 71%. 3). Perception of teachers on the managerial patterns principal and teacher motivation positive effect on the performance of teachers. This is proven by the F test > obtained namely 3.867> 3.17 and 0.027 significance probability value <0.05. The result of the coefficient of determination ( ) 32.9% while the remaining value 67,1% influenced by other factors.